Ump couple lecturer won UMP quality and Innovation day 2014 Publication Award - Shalfarina, Shahriman (Penerbit UMP, 2014)

(untitled)
Good quality content, clear learning criteria and well-structured language were the engaging features that won the book titled, 'Enzymatic Membrane Reactor for Fine Chemical Production' the Publication Prize at UMP Quality and Innovation Day 2014 Prize last May.